Assessing the impact of hydro-climatic factors on surface water quality: A global review and synthesis - Apoorva Bamal; Md Galal Uddin; Agnieszka I. Olbert (Journal of Hydrology: Regional Studies)
Study region: Global, with emphasis on diverse climatic and geographic regions impacted by hydro-climatic variability. Study focus: This review investigates the influence of hydro-climatic parameters—such as precipitation, temperature, runoff, and streamflow—on surface water quality (WQ), incorporating both natural climatic variability and anthropogenic climate change. It synthesizes findings from 71 peer-reviewed studies using PRISMA guidelines, focusing on methodological approaches and key hydro-climatic drivers affecting WQ. New hydrological insights for the region: Findings reveal that hydro-climatic factors significantly impact individual WQ parameters and overall WQ status. While precipitation and temperature are widely studied, variables like windspeed and relative humidity remain underexplored, potentially limiting the understanding of climate–WQ interactions. Most studies rely on statistical or hydrological models, which often fail to capture complex, nonlinear relationships. The integration of advanced machine learning (ML) and artificial intelligence (AI) methods shows promise in improving predictive accuracy and uncovering hidden patterns. However, few studies assess the cumulative or synergistic effects of multiple hydro-climatic variables. Future research should adopt multidisciplinary, integrated modeling frameworks to better represent dynamic interactions under climate change scenarios. Long-term environmental monitoring and adaptive management strategies are essential for enhancing WQ resilience. To the best of the authors’ knowledge, this review is among the first to comprehensively assess the interplay of multiple hydro-climatic drivers on surface WQ, offering critical insights for more informed water resource management and climate adaptation policy.